Day or overnight transfusion in critically ill patients: does it matter?. Issue 3 (2nd February 2018) - Aubron, C.; Kandane‐Rathnayake, R. K.; Andrianopoulos, N.; Westbrook, A.; Engelbrecht, S.; Ozolins, I.; Bailey, M.; Murray, L.; Cooper, D. J.; Wood, E. M.; McQuilten, Z. K.; ,; et al.
Abstract : Background and objectives: The timing of blood administration in critically ill patients is first driven by patients' needs. This study aimed to define the epidemiology and significance of overnight transfusion in critically ill patients. Materials and methods: This is a post hoc analysis of a prospective multicentre observational study including 874 critically ill patients receiving red blood cells, platelets, fresh frozen plasma (FFP) or cryoprecipitate. Characteristics of patients receiving blood only during the day (8 am up until 8 pm) were compared to those receiving blood only overnight (8 pm up until 8 am). Characteristics of transfusion were compared, and factors independently associated with major bleeding were analysed. Results: The 287 patients transfused during the day only had similar severity and mortality to the 258 receiving blood products overnight only. Although bleeding‐related admission diagnoses were similar, major bleeding was the indication for transfusion in 12% of patients transfused in daytime only versus 30% of patients transfused at night only ( P < 0·001). Similar total amount of blood products were transfused at day and night (2856 versus 2927); however, patients were more likely to receive FFP and cryoprecipitate at night compared with daytime. Overnight transfusion was independently associated with increased odds of major bleeding (odds ratio, 3·16, 95% confidence interval, 2·00–5·01). Conclusion: Transfusion occurs evenly across day and night in ICU; nonetheless, there are differences in type of blood products administered that reflect differences in indication. Critically ill patients were more likely to receive blood for major bleeding at night irrespective of admission diagnosis.